2013
DOI: 10.2332/allergolint.12-oa-0492
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CTLA4+ and Foxp3+ CD25highCD4+ Cells in Induced Sputum from Patients with Mild Atopic Asthma

Abstract: Airway, but not circulating, Tregs are decreased in mild atopic asthmatics, and are negatively correlated to an increase of airway eosinophilic inflammation and AHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
3
18
0
1
Order By: Relevance
“…In addition, the suppression of runx1 occurred at an earlier timepoint (1 day) than for foxp3 (4 days), an outcome that is consistent with the earlier requirement for runx1 in the regulatory T-cell pathway (Chatila, 2008). Reduced foxp3 expression has also been recently associated with asthma and immune-mediated skin diseases (Kawayama et al, 2013;Quaglino et al, 2013). Although the exact role of T H 17 cells in allergic disease is still unclear, available data suggest that this T-cell lineage may also contribute to the pathogenesis of atopic diseases such as asthma and contact dermatitis.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, the suppression of runx1 occurred at an earlier timepoint (1 day) than for foxp3 (4 days), an outcome that is consistent with the earlier requirement for runx1 in the regulatory T-cell pathway (Chatila, 2008). Reduced foxp3 expression has also been recently associated with asthma and immune-mediated skin diseases (Kawayama et al, 2013;Quaglino et al, 2013). Although the exact role of T H 17 cells in allergic disease is still unclear, available data suggest that this T-cell lineage may also contribute to the pathogenesis of atopic diseases such as asthma and contact dermatitis.…”
Section: Discussionmentioning
confidence: 54%
“…Our results [32,40] suggest that airway Tregs may be decreased, and that the decreased Tregs may be associated with increased airway inflammation in asthma. This inflammation may contribute to bronchoconstriction.…”
Section: Kinetics Of Tregs After Allergen Challenge In Adult Atopic Mmentioning
confidence: 69%
“…The induced sputum technique also can assess the effectiveness of newly developed agents [30,31]. The number of airway eosinophils in patients with mild asthma was significantly higher than non-asthmatic control subjects (control subjects) ( Figure 1A and 1B) [32]. The number of airway eosinophils was also increased in patients with asthma after allergen, but not methacholine (Mch) challenge ( Figure 1C) [33].…”
Section: Evaluation Of Airway Inflammation and Hyperresponsivenessmentioning
confidence: 99%
“…Peripheral blood collected from asthmatic showed decreased expression of CD4+CD25+ than in non-asthmatics (126). Other studies highlighted that Tregs were decreased in samples collected from the airways of atopic individuals (180). Shi et al, also observed that patients with moderate to severe asthma showed decreased number of CD4+CD25+ Tregs and had increased Th2 responses (181).…”
Section: Regulatory Mediatorsmentioning
confidence: 96%